MONITORING THE QUALITY OF KNOWLEDGE IN THE PERSON-ORIENTED EDUCATION SYSTEM - Yunusova, Gulnoza Abduxalikovna (INTERNATIONAL CONFERENCES, 2023)
the paper states how the use of monitoring in identifying the quality of students’ knowledge in the system of lifelong student-oriented education will help improve the effectiveness of training and provide an assessment of students’ knowledge and skills adequate to the requirements of the continuity of higher professional education.